Does perioperative electroacupuncture reduce postoperative pain in dogs undergoing ovariohysterectomy? - Iwe, Celine; Schiele, Anika; Passenegg, Vanessa; Corona, Daniele; Bettschart-Wolfensberger, Regula; Heitzmann, Vanessa (Frontiers in Veterinary Science, 2025)
IntroductionThis study aimed to investigate the analgesic efficacy of perioperative electroacupuncture in fifty-six healthy female dogs undergoing ovariohysterectomy as part of a catch-neuter-release project.Materials and methodsTen minutes after sedation with 20 μg/kg medetomidine combined with 0.3 mg/kg butorphanol intramuscularly, the dogs were randomly allocated into two groups and received either electroacupuncture (EA, n = 27) or sham acupuncture (C, n = 29) treatment for 10 min (after sedation until the end of the surgery) at 6 different acupuncture points LI-4 (Large intestine 4), LIV-3 (Liver 3), ST-36 (Stomach 36), SP-6 (Spleen 6) bilateral. After administration of 0.2 mg/kg meloxicam and anesthesia induction with 2 mg/kg ketamine intravenously, ovariohysterectomy was performed by the same experienced surgeon using a midline surgical approach in dorsal recumbency. Pain was evaluated by two blinded and independent anesthetists using the Short Form of the Multimodal Glasgow Composite Pain Scale (mCMPS-SF) before sedation (T0), and three (T3), six (T6), and 24 h (T24) after anesthesia induction.ResultsPostoperative pain scores did not differ significantly between the groups (p = 0.36), but increased significantly three (T3) (p = 0.001) and six (T6) (p = 0.001) hours after surgery compared to before sedation and 24 h postoperative in both groups. Three hours after surgery (T3), 89.4% and six hours postoperatively (T6), 71.4% of the dogs in both groups exceeded the analgesic intervention threshold of the mCMPS-SF, indicating the need for rescue analgesia.DiscussionThe results of the study indicate that perioperative electroacupuncture treatment did not improve postoperative pain in dogs undergoing ovariohysterectomy. Therefore, a 10-min electroacupuncture treatment may be insufficient to provide effective postoperative analgesia. The pain assessment in feral dogs was notably impacted by anxious behavior, which may have influenced the final outcome The pain threshold was exceeded in ¾ of the dogs in the early postoperative phase (T3, T6), suggesting that the widely used anesthesia protocol consisting of butorphanol, ketamine and medetomidine in combination with meloxicam may not provide long-lasting and sufficient pain relief.